Pengaruh Variasi Jenis Busi dan Bahan Bakar M20 (Premium 80%-Metanol 20%) Terhadap Performa Sepeda Motor Yamaha Nmax 155 - Hartanto, Iqbal; Ghurri, Ainul; Nindhia, Tjokorda Gde Tirta (Teknik Desain Mekanika, 2021)
Abstractt In order to reduce the use of fossil fuels when the number of motorcycles increases, it is necessary to look for renewable and easily available fuels, one of which is Premium 80%-methanol 20% (M20) mixed fuel. In addition to the use of fuel that we must pay attention to, spark plugs as a vital component of the engine also receive the impact of the use of fuel used in the engine. The visual condition of the spark plug can also reflect whether or not the combustion process in the engine is good. The purpose of this study was to analyze the use of Premium 80%-methanol 20% (M20) fuel on the performance of a Yamaha Nmax 155 motorcycle using standard, platinum and iridium spark plug variations. In this study, the authors also compared the performance of a Yamaha Nmax 155 motorcycle using Pertamax fuel with standard, platinum and iridium spark plug variations. The results of this study indicate that the use of Premium 80%-methanol 20% fuel leaves carbon impurities and the least reduction in the value of the resistor at the spark plug when compared to lower methanol concentrations. The performance produced by the Yamaha Nmax 155 motorcycle has the largest power of 13.13 hp using Premium 80%-Methanol 20% (M20) fuel using iridium spark plugs and the largest torque of 14.09 Nm is obtained with Premium 80%-Methanol 20 fuel. % (M20) with standard spark plugs. For the smallest power and torque obtained with Pertamax fuel, each 12.55 hp with platinum spark plugs and 12.07 N.m with standard spark plugs. Keywords: Premium-Methanol Fuel, Power and Torque, Various Types of Spark Plugs